Scale microstructure study of Bluering angelish, Pomacanthus annularis (Bloch, 1787) from Veraval fishing harbour, Gujarat, India - Tandel Rutvikkumar P; Sheetal K Bharda; D.T. Vaghela; Ritesh V. Borichangar; Dhaval Jungi; N A Pargil; Rajesh Kumar (Journal of Indian Fisheries Association, 2023)
Despite one of the important species of coral reef environment, information regarding scale morphology of Pomacanthids is rare. In present study, first attempt was made to document various scale characteristics of Bluering angelfish, Pomacanthus annularis (Bloch, 1787) from Veraval fishing harbour, Gujarat, India. For detailed study, scales from different body area: head scale, belly scale and caudal scale were observed and measured with the application of Scanning Electron Microscopy (SEM). The contemporary analysis of scale morphology recorded spinoid type cycloid scale in all over body regions in considered species. Besides scale type some consistent scale characteristics from different body regions such as; semi circular shaped and posteriorly located focus, a striate form of interradial circuli, rectangular shaped and round ended lepidonts on circuli of anterior field, elongated and triangular shaped spinous structure on the posterior field were found distinctive traits of studied species. Based on the obtained result, the study concluded that certain features on a scale can be potentially employed as reliable taxonomic tools. Moreover, morphometric indices (J-indices, radii count, scale size) were additionally considered as an effectual tool for species discrimination, even in the case of closely related species.